Gender and Positive Politeness in Facebook Communication - Dąbrowska, Marta (Armenian Folia Anglistika, 2012)
The article analyzes a number of linguistic strategies which act as bearers of positive politeness (in male and female communications) in Facebook social network. Summing up the results of the investigation the author concludes that linguistic expressions among male and female users differ significantly not only in everyday or semi-formal contexts, but in modern computer language at large.